Antimicrobial, antioxidant, α-amylase and α-glucosidase inhibitory activities of a chemically characterized essential oil from Lavandula angustifolia Mill.,: in vitro and in silico investigations - Jeddi, Mohamed; El Hachlafi, Naoufal; El Fadili, Mohamed; Benkhaira, Nesrine; Al-Mijalli, Samiah Hamad; Kandsi, Fahd; Abdallah, Emad M; Ouaritini, Zineb Benziane; Bouyahya, Abdelhakim; Lee, Learn-Han *; Zengin, Gokhan; Mrabti, Hanae Naceiri; et al. (Elsevier, 2023)
Lavandula angustifolia is a medicinal plant widely known by its medicinal virtues against various pathogenesis, including diabetes, cancer and infectious diseases. In this study we aimed to explore the volatile profile of L. angustifolia essential oil (EO) as well as its in vitro and in silico antimicrobial, antioxidant and antidiabetic effects. The chemical constituents were investigated through Gas Chromatography-Mass Spectrometry (GC/MS) analysis. Three complementary antioxidant tests, namely DPPH, FRAP and inhibition of lipid peroxidation assays were used to reveal the antioxidant ability of L. angustifolia EO. The antidiabetic effect of this oil was determined using α-amylase and α-glucosidase enzymes. Molecular docking and ADMET analysis were used to confirm the experimental effects.